Searchable encryption with randomized ciphertext and randomized keyword search - Calderini, Marco; Longo, Riccardo; Sala, Massimiliano; Villa, Irene (Journal of mathematical cryptology, 2024)
The notion of public-key encryption with keyword search (PEKS) was introduced to search over encrypted data without performing any decryption. In this article, we propose a PEKS scheme in which both the encrypted keyword and the trapdoor are randomized so that the cloud server is not able to recognize identical queries . Our scheme is secure in the single-user setting and secure in the multi-user setting with a stronger security, i.e., with